2006
DOI: 10.1002/art.21621
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible genetic associations between candidate genes and clinical knee osteoarthritis in men and women

Abstract: Objective. Osteoarthritis (OA) is recognized to have a genetic component, and in this study, we aimed to replicate in a case-control study of men and women with clinical knee OA genetic associations in 12 candidate genes previously reported to be associated with OA.Methods. Twenty-five single-nucleotide polymorphisms were genotyped in 298 men and 305 women ages 50-86 who were diagnosed as having knee OA, as assessed both clinically and radiographically, and in 297 men and 299 women matched for age and ethnicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
115
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(122 citation statements)
references
References 15 publications
3
115
0
4
Order By: Relevance
“…These include age, sex, genetics, ethnicity, behavioral influences, obesity and occupation 17. A genetic contribution to OA has been suggested in several epidemiologic and other studies 31819. The genetics of OA are complex and not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…These include age, sex, genetics, ethnicity, behavioral influences, obesity and occupation 17. A genetic contribution to OA has been suggested in several epidemiologic and other studies 31819. The genetics of OA are complex and not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…In cartilage, BMP-2 has both anabolic and catabolic effects by stimulating expression of ECM proteins, such as collagen type II, and matrix degrading enzymes, such as MMPs (Blaney Davidson et al 2007; van der Kraan et al 2010). Single-nucleotide polymorphisms (SNPs) in BMP2 were found in OA patients but their functional relevance is unknown (Valdes et al 2004(Valdes et al , 2006. The expression levels of BMP7 decline with increasing age and with progression of OA (Chubinskaya et al 2002), and the expression domains of GDF5 and GDF6 expand in adult human OA articular cartilage (Erlacher et al 1998).…”
Section: Dysregulation Of Tgf-b or Bmp Signaling In Catabolic Bone DImentioning
confidence: 99%
“…Three possible reasons accounting for the inconsistency of results are the different ethnicities of the subjects investigated, the sites of OA that were chosen, and the sex of the patients and controls. We recently reported that genetic associations with knee OA are strongly influenced by sex (32). In the current study, we assessed genetic variants in the above-mentioned 5 genes in an ethnically homogeneous cohort of patients with knee OA, analyzing men and women separately.…”
mentioning
confidence: 96%